Pengaruh Metode Pemupukan terhadap Pertumbuhan Cabai Rawit (Capsicum frutescens L.) Varietas Taruna Intercropping Tanaman Chaya - Ananda, Anatasia P; Gustiar, F; Ammar, M; Susilawati, Susilawati (Seminar Nasional Lahan Suboptimal, 2022)
Ananda AP, Gustiar F, Ammar M, Susilawati S. 2022. The effect of fertilization methods on the growth of cayenne pepper (Capsicum frutescens L.) taruna varieties intercropping of chaya plants. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang  27 Oktober 2022. pp. 800-808.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Optimization of land through the use of intercropping between Chaya plants and chili plants using several fertilization methods is expected to increase the production of horticultural crops. This study aimed to determine the effect of intercropping patterns and fertilization methods on the growth of cayenne pepper (Capsicum frutescens L.) Taruna variety. The experimental design used was a Split Plot Design which consisted of 2 main plots, namely: Intercropping plot (T1), Monoculture plot (T2), with 4 subplots treated with fertilization method, and 3 replications. The four treatments of the fertilization method were: Bulk (P1), Broadcasting (P2), Spot placement (P3), Spray (P4). The data obtained from the observations and measurements will be analyzed using variance and regression tests. The results showed that the application of fertilization did not have a significant effect on the growth of cadet varieties of chili. The growth of chili plants in monoculture was better than the intercropping pattern on the parameters of the number of leaves, the level of greenness of the leaves, the diameter of the stem and the diameter of the crown, while the plant height and leaf thickness were better in the intercropping pattern.